2022
DOI: 10.1093/jisesa/ieab103
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenism in Antennal Sensilla Among Different Adult Morphs of Nonhost-Alternating, Holocyclic Sitobion avenae (Hemiptera: Aphididae)

Abstract: Aphids, mainly distributed in temperate zones, exhibit seasonal generation-alternating phenomena. Across the life cycle, different morphs are produced. Sitobion avenae (Fabricius 1775) is a major pest of wheat worldwide. To elucidate olfactory perception of morph-specific behavior across their life cycle, we investigated antennal sensilla among seven morphs using scanning electron microscopy. Trichoid, placoid, coeloconic, and campaniform sensilla were identified. Trichoid sensilla, big multiporous placoid sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 44 publications
3
7
0
Order By: Relevance
“…The antennae of S. heracei were longer in males than in sexual females mainly due to flagellum length differentiation between the sexes. A similar result was also found in S. avenae [ 16 ]. In Macrosiphoniella sanborni , the apterous viviparous female had longer antennae than the alate [ 29 ].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The antennae of S. heracei were longer in males than in sexual females mainly due to flagellum length differentiation between the sexes. A similar result was also found in S. avenae [ 16 ]. In Macrosiphoniella sanborni , the apterous viviparous female had longer antennae than the alate [ 29 ].…”
Section: Discussionsupporting
confidence: 88%
“…Antennal sensilla are specialized components of the antennal cuticles and function as organs detecting both external and internal stimuli to regulate behavior via the nervous system [ 15 ]. Although the morphology of antennae and sensilla has been described in a few species, such as M. persicae , Acyrthosiphon pisum , Sitobion avenae with both viviparous and bisexual morphs [ 16 , 17 , 18 ], A. gossypii and A. glycine with viviparous morphs and the male only [ 19 , 20 ], studies focusing on the sexual differentiation of antennae in males compared with females are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Antennae in most aphid species typically contain six segments, including a scape, a pedicel, and a flagellum with 4 flagellomeres (Song et al, 2020 ; Wu et al, 2022 ). In this study, six segments were observed in C. cedri, E. lanigerum , and T. trifolii , but exhibited various lengths, thicknesses, and shapes.…”
Section: Discussionmentioning
confidence: 99%
“…In aphids, antennae are the main olfactory organs, and are filiform and composed of 5–6 segments, including a scape, a pedicel, and a flagellum with 3–4 flagellomeres (Kanturski et al, 2017 ; Song et al, 2020 ; Wu et al, 2022 ). The main sensory structures are called rhinaria (Wensler, 1974 , 1977 ; Bromley and Anderson, 1982 ; Pickett et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation